Ultraviolet Lights Effect on Farmer Health and Productivity: Literature Review - Enggal Hadi Kurniyawan; Angela Irena Junanda; Hersanti Maulia Putri H; Meri Katrin Dwi Cayani; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (Nursing and Health Sciences Journal (NHSJ), 2023)
Cumulative exposure to solar UV radiation is linked to chronic skin and eye diseases such as skin cancer, photoaging, actinic keratosis, pterygium, cataracts, and possibly macular degeneration. This study aims to determine farmers' knowledge about UV rays on eye health in anticipating the dangers of excessive UV rays and increase farmer awareness of the sources and risks of UV rays for eye health. The method used is a literature review to examine the effects of UV Lights on the health and productivity of farmers in more depth. This literature search was conducted until March 19, 2023, using the PubMed and Science Direct article search engines, with the following search terms using the BOOLEAN Operator technique: "UV Light effects" AND "Farmer," "UV Rays" AND "Farmer," "Heat Effects" AND "Farmer." The analysis carried out in this study concluded that outdoor workers (PL), especially those working in sectors such as agriculture, construction, and fishing, are at high risk of exposure to the harmful effects of UV rays. Fishermen and farmers have a higher risk of cataracts due to excessive UV exposure to the eyes. One of the prevention efforts that can be done is health promotion regarding farmers' knowledge about UV light on eye health in anticipating the dangers of excessive UV light and increasing farmer awareness about the sources and risks of UV light for eye health. Health workers, especially nurses, can provide health services through supportive therapy to overcome physical and psychological problems in cataract patients and helps anticipate the dangers of UV rays at work.